New families of star-supermagic graphs - Anak Agung Gede Ngurah (Indonesian Combinatorial Society (InaCombS), 2020)
A simple graph G admits a K1,n-covering if every edge in E(G) belongs to a subgraph of G isomorphic to K1,n. The graph G is K1,n-supermagic if there exists a bijection f : V(G) ∪ E(G) → 1, 2, 3,..., |V(G) ∪ E(G)| such that for every subgraph H' of G isomorphic to K1,n, ∑v ∈ V(H') f(v) + ∑e ∈ E(H') f(e) is a constant and f(V(G)) = 1, 2, 3,..., |V(G)|. In such a case, f is called a K1,n-supermagic labeling of G. In this paper, we give a method how to construct K1,n-supermagic graphs from the old ones.